Zarządzanie personelem jako element systemu bezpieczeństwa ekonomicznego biznesu (Research Bulletins of the Faculty of Economic Sciences, 2018)
The purpose of the work is to develop theoretical and methodological approaches and practical recommendations on the management of the personnel of the company as a component of ensuring the economic security of companies. The most important strategic directions of ensuring economic safety of the entity is identification, prevention, neutralization, suppression, localization, reflection of dangers and threats, and in case of need – damage compensation, recovery objects of the protection injured with illegal actions, negligence, force-majeurе circumstances, etc.
Keywords: counterparties, receivables, debt quality, matrix